2017
DOI: 10.1289/ehp1302
|View full text |Cite
|
Sign up to set email alerts
|

Serum Polybrominated Biphenyls (PBBs) and Polychlorinated Biphenyls (PCBs) and Thyroid Function among Michigan Adults Several Decades after the 1973–1974 PBB Contamination of Livestock Feed

Abstract: Background:In 1973–1974, Michigan residents were exposed to polybrominated biphenyls (PBBs) through an accidental contamination of the food supply. Residents were enrolled in a registry assembled after the incident, and they and their children participated in follow-up studies to assess subsequent health outcomes.Objectives:We evaluated associations between serum PBBs and polychlorinated biphenyls (PCBs) and markers of thyroid function among Michigan adults.Methods:Serum concentrations of four PBB and four PCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 70 publications
4
48
3
Order By: Relevance
“…This is consistent with early studies that that showed that 35-40% of Michigan farmers who had eaten PBB-contaminated food had a significant reduction in in vitro immune function [69]. While no studies have looked at PBB's association with the development of autoimmune disorders, studies in this cohort have found PBB exposure is associated with the development of hypothyroidism (which is commonly caused by an autoimmune disorder) in both men and women, although neither of these analyzed hypothyroidism by type [24,25]. Additionally, when the signal for the CpGs associated with low grade inflammation was compared to the signal from PBB, they were correlated, and PBB was associated with the proportion of B cells, even after controlling for age, sex, and lipid levels.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is consistent with early studies that that showed that 35-40% of Michigan farmers who had eaten PBB-contaminated food had a significant reduction in in vitro immune function [69]. While no studies have looked at PBB's association with the development of autoimmune disorders, studies in this cohort have found PBB exposure is associated with the development of hypothyroidism (which is commonly caused by an autoimmune disorder) in both men and women, although neither of these analyzed hypothyroidism by type [24,25]. Additionally, when the signal for the CpGs associated with low grade inflammation was compared to the signal from PBB, they were correlated, and PBB was associated with the proportion of B cells, even after controlling for age, sex, and lipid levels.…”
Section: Discussionsupporting
confidence: 83%
“…Total lipid level was calculated in this cohort as part of previous studies [25]. A Triglyceride Quantification Assay Kit (Abnova Corporation) was used to measure the total triglyceride content in serum, and a Cholesterol Assay Kit (Caymen Chemical Company) was used to measure total cholesterol content in serum.…”
Section: Lipid Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of continued effort to enroll members and inform the community of research findings, members of the PBB registry were mailed invitations to attend community meetings held throughout the state where recruitment was conducted between 2012 and 2015. Community meetings were also advertised in the local press; thus, individuals from the original registry as well as others who had lived in the state of Michigan during the time of contamination (1973)(1974) or were offspring of those who lived in the state during that time 41 attended and subsequently participated. For this study, participants had to be women between the ages of 18 and 59, had to have completed a detailed reproductive health questionnaire, and had to have a blood draw with recent PCB and PBB concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The separation of halogenated benzenes in oil samples is a major issue in the eld of environmental chemistry, since many halogenated benzenes are in waste oil and are highly toxic. [73][74][75] Therefore, the LC separation of halogenated benzenes has great importance in environmental chemistry and shows its potential for separating toxic aromatic halogens, such as polychlorinated biphenyls and polybrominated biphenyls.…”
Section: One-pot Separation Of the Entirety Of Brominated Benzenesmentioning
confidence: 99%